Archaeology in Asia Minor - Mellink, Machteld J.
espec. Paleolithic Sites: Küçükçekmece, Karain, Tozkoparan, Tilkikaya, Avla Dağ, Çorum, Erzurum, Bursa — Neolithic and Chalcolithic Sites: Çatalhüyük, Suberde, Kürtün İni, Avla Dağ, Can Hasan — Bronze Age Sites: Kültepe, Boğazköy, Alaca Hüyük, Acemhüyük, Karahüyük, Tilmen Hüyük, Gidıkh Hüyük, Yalıncak-Kocumbeli Karayavşan, Gordion, Beycesultan, Yuva, Karataş-Semayük, Iasos, Bodrum-Yatağan, Denizli Area, Silivri-Kanallı Köprü — Urartian Sites: Altıntepe, Çavuştepe, Van-Toprakkale, Ernis, Adılcevaz, Kayalıdere — Neo-Hittite and Phrygian Sites: Malatya, Karatepe, Kültepe, Ankara-Yalıncak, Gordion, Mihalıççık, Düver, Afyon-Çavdarlı Hüyük — Classical Sites.